Pedagogies of care, care-full epistemological practice and 'other' caring subjectivities in enabling education. Issue 5 (4th July 2018) - Motta, Sara C.; Bennett, Anna
ABSTRACT: This article explores and conceptualises the emergent and historic presence of a feminised pedagogical praxis in Australian Enabling (university access) programs. Analysing a participatory project at a regional university that sought to map these pedagogies, it specifically aims to visibilise the complexities of careful pedagogical practices which challenge deficit and assimilationist renditions of equity and inclusion, and which foster the possibilities for re-narrativisations of self, community and other. Such pedagogical practices not only develop ethics and practices of care but foreground careful recognition of the epistemological contributions of subjects from non-traditional backgrounds. These pedagogies of difference and other pedagogical subjectivities are situated within a broader context in which hegemonic careless masculinities render these transformative feminised pedagogies invisibilised, devalued and denigrated. Our paper concludes with suggestions for the ways in which these pedagogies of care and other caring subjectivities might be nurtured and rendered powerful within our current context.